Ferroelectric switching dynamics in 0.5Ba(Zr0.2Ti0.8)O-3-0.5( Ba0.7Ca0.3)TiO3 thin films - Silva, J. P. B. (2018)
In this work, the ferroelectric characteristics of 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3)TiO3 (BCZT) thin films grown on 0.7 wt. % Nb-doped (001)-SrTiO3 (Nb:STO) single-crystal have been investigated. High-resolution transmission electron microscopy and electron energy loss spectroscopy revealed a very sharp Nb:STO/BCZT interface, while selected area electron diffraction revealed the epitaxial growth of the BCZT layer on the Nb:STO substrate. The ferroelectric nature of the BCZT films have been investigated by piezoresponse force microscopy and hysteresis loops. The effect of electric field on polarization switching kinetics has been investigated and has been analyzed by the nucleation limited switching model with a Lorentzian distribution function. The local field variation was found to decrease with the increase in the electric field, and thus, the switching process becomes faster. The peak value of the polarization current and the logarithmic characteristic switching time exhibited an exponential dependence on the inverse of electric field. This model gave an excellent agreement with the experimental polarization reversal transients throughout the whole time range.